9(9x-5)+9=4x-2

Simple and best practice solution for 9(9x-5)+9=4x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(9x-5)+9=4x-2 equation:


Simplifying
9(9x + -5) + 9 = 4x + -2

Reorder the terms:
9(-5 + 9x) + 9 = 4x + -2
(-5 * 9 + 9x * 9) + 9 = 4x + -2
(-45 + 81x) + 9 = 4x + -2

Reorder the terms:
-45 + 9 + 81x = 4x + -2

Combine like terms: -45 + 9 = -36
-36 + 81x = 4x + -2

Reorder the terms:
-36 + 81x = -2 + 4x

Solving
-36 + 81x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-36 + 81x + -4x = -2 + 4x + -4x

Combine like terms: 81x + -4x = 77x
-36 + 77x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-36 + 77x = -2 + 0
-36 + 77x = -2

Add '36' to each side of the equation.
-36 + 36 + 77x = -2 + 36

Combine like terms: -36 + 36 = 0
0 + 77x = -2 + 36
77x = -2 + 36

Combine like terms: -2 + 36 = 34
77x = 34

Divide each side by '77'.
x = 0.4415584416

Simplifying
x = 0.4415584416

See similar equations:

| k-4-4=7-4k | | 8+4(-5x)=6-3(1-3x) | | 2-1/4x=16 | | 17-k=9 | | -15=-2(x-2) | | 4(2x+2)-8X=12 | | 6x/5(6-4)=3x+8 | | 7p=5+.10p | | 7x-9x=48 | | 1/3(3X+15) | | 3y+2+2y=5+y | | 2.9+5=4.7-7.6 | | 4w^2=36w | | 0.55x+0.05(10-x)=0.10(45) | | 8d-255=3d | | 5+12m-2=7m+83-5m | | -4/5-6=14 | | x^2-10x-43=0 | | 15+22=-7+18 | | 4=4m-4 | | 60/221=l | | 0.45(12)+0.05x=0.15(12+x) | | 3(x+3)-(3x+4)+4x+3=6(x-3) | | 2000=(2000-150)-(225*3.50)-x | | -3(2x-3)=-6x+19 | | 221/60=l | | 1.25(s+72)=273.75 | | 3(7x-21)=-4 | | 6(-2-x)=-3(2x+5) | | -8b+31=-7(2b-7) | | 3(3v-4)=51 | | 1.25(s+72)=250 |

Equations solver categories